Moderasi Beragama Melalui Pendidikan Lintas Budaya: Menguatkan Profil Pelajar Pancasila di UPTD SMAN 1 Nosu - Halim, Muhammad Hamka; Alwi, Alimin; Najamuddin, Najamuddin (Indo-MathEdu Intellectuals Journal, 2025)
This study aims to describe the implementation of Cross-Cultural Education in instilling the value of Religious Moderation and to identify supporting factors, obstacles, and strategies for strengthening the Pancasila Student Profile at UPTD SMAN 1 Nosu, Mamasa Regency. The research uses a qualitative approach with a case study method. Data were collected through in-depth interviews, participatory observation, and document analysis of the principal, vice principal for curriculum, teachers, student council president, and students from various religious and cultural backgrounds. Data analysis was conducted interactively through the stages of reduction, presentation, and conclusion drawing using the Miles and Huberman model. The results of the study indicate that the implementation of Cross-Cultural Education is effective through intracurricular, cocurricular, and extracurricular activities that foster the values of mutual cooperation and global diversity. The value of religious moderation is integrated through a contextual approach and cross-curricular projects. Supporting factors include inclusive school policies, teacher competence, student participation, and a conducive learning environment, while the main obstacles are limited facilities, low literacy in moderation, social resistance, and a crowded curriculum.